2009
DOI: 10.1155/2009/973206
|View full text |Cite
|
Sign up to set email alerts
|

Closure of a Nonhealing Gastrocutaneous Fistula Using Argon Plasma Coagulation and Endoscopic Hemoclips

Abstract: A case in which a gastrocutaneous fistula developed after percutaneous endoscopic gastrostomy tube placement is presented. The fistula was first managed conservatively, then was closed by argon plasma coagulation and hemoclip placement. The patient was observed and was discharged once the gastrocutaneous fistula closed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Therefore, our decision to combine the endoscopic closure procedure with surgical de-epithelialisation may have contributed to the successful outcome. Other non-surgical options for de-epithelialisation in the literature have included electro and chemical cautery, argon beam photocoagulation and biopsy removal6 7 10 13 15; these could potentially be used in conjunction with the Padlock clip as an alternative to surgical excision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our decision to combine the endoscopic closure procedure with surgical de-epithelialisation may have contributed to the successful outcome. Other non-surgical options for de-epithelialisation in the literature have included electro and chemical cautery, argon beam photocoagulation and biopsy removal6 7 10 13 15; these could potentially be used in conjunction with the Padlock clip as an alternative to surgical excision.…”
Section: Discussionmentioning
confidence: 99%
“…Successful outcomes have been reported for GCF with endoscopic clip closure6–12 and endoscopically assisted suturing techniques 13–15. A combined approach to de-epithelialise the tract in addition to mechanical endoscopic closure has been advocated in the majority of published cases,6 7 10 13 15 thereby mimicking the surgical approach, with good results, albeit limited to small series and case reports. Given that endoscopic clip closure is less invasive than endoscopically assisted suturing, it is often the first-line approach.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for persistent fistulas after gastrostomy removals include usual factors that would perpetuate a fistula such as infection at the site, a short, wide tract in a thin person with little distance between the stomach and skin, and a very long-standing gastrostomy tube. [81][82][83] Janik et al found that a gastrostomy tube duration longer than 8 months was associated with a persistent fistula in their pediatric population. 81 If a gastrocutaneous fistula is persisting, then initial measures include using chemical cautery with silver nitrate sticks and placing the patient on twice daily proton pump inhibitors and possible prokinetic agents as well.…”
Section: Gastrocutaneous Fistula After Removalmentioning
confidence: 99%
“…Minimally invasive techniques, including gastric mucosa endoclipping, fibrin glue, and fistula tract lining disruption using a curette or electrocautery device, have also been described and may be attempted prior to proceeding with surgery. [75][76][77][78] Anecdotally, placing a purse-string suture beneath the skin in the subcutaneous tissue may be added to the endoclipping of the mucosal defect to promote closure.…”
Section: Persistent Fistula Following Removalmentioning
confidence: 99%